Concerning imported cases of cholera in the city of Almaty, Kazakhstan, 2017 - Z. A. Sagiev; R. S. Musagalieva; A. A. Abdirasilova; T. Z. Ayazbaev; M. M. Kul’baeva; A. B. Mоldagasimova; A. S. Zhunusova; I. B. Utepova; E. Zh. Begimbaeva; U. A. Izbanova; G. M. Omasheva; Z. S. Turliev; et al. (Проблемы особо опасных инфекций, 2018)
In 2017, from October 15 to November 21, 5 cholera cases imported from India – 3 patients and 2 carriers of V. cholerae – were recorded in Almaty. The patients recovered from the disease. Objective of the study was to characterize the imported cases of cholera and investigate the properties of cholera vibrio strains isolated from patients and carriers of V. cholerae. Materials and methods. Revised were the medical records; blood sera, feces from patients and contact persons were assayed. Studied were sensitivity spectrum to antibacterial preparations of isolated V. cholerae strains according to the “Methodological guidelines on laboratory diagnosis of cholera”, dated September 27, 2010; No 252. Epidemiological, microbiological, immunological and molecular-genetic methods were applied for investigation. Results and conclusions. Consequently to molecular genetic studies, genes of specificity, wbeN and toxicity (epidemic significance), ctxA, tcpA were detected in samples from 3 patients and 2 contact persons. The isolated strains were identified as Vibrio cholerae O1 Eltor Inaba in two cases, and in one case – as Vibrio cholerae O1 Eltor Hykoshima, Heiberg group I, toxigenic, hemolysis negative in Greig test, virulent, highly sensitive to ciprofloxacin, doxycilin, erythromycin, tetracycline and moderately sensitive to levomycetin. It was established that the country of export in all the cases was India. Relevant anti-epidemic and preventive measures were undertaken to localize and eradicate the foci in order to prevent possible threat of epidemic spread of infections among the population.